Programa SAFO (Suporte Afirmativo de Fortalecimento Online): intervenção individual online para mulheres lésbicas vítimas de violência entre parceiras íntimas - Furukawa, Letícia Yuki de Araujo (Universidade Federal de São Carlos, 2026)
The present research investigated intimate partner violence (IPV) among lesbian women through four complementary studies: (1) psychosocial characterization, (2) comprehension of victimization experiences, (3) development of a psychoeducational intervention (SAFO Program), and (4) feasibility analysis. Study 1 included 44 women who completed psychosocial characterization questionnaires alongside the AUDIT, CTS-2, and PCL-5 scales. The obtained data indicated that greater severity of post-traumatic stress disorder (PTSD) symptoms was associated with higher alcohol consumption. Furthermore, participants with a prior clinical diagnosis consumed significantly more alcohol. A predictive model demonstrated that alcohol consumption and sexual coercion perpetrated by a partner were significant predictors of PTSD symptom exacerbation. Study 2 involved three women with a history of intimate partner violence. All participants engaged in a synchronous remote interview. The findings indicated a difficulty in recognizing abusive situations, particularly psychological violence. Even after terminating the relationships, reported consequences included symptoms of depression, anxiety, panic, and disturbances in sleep and eating patterns. Informal support networks (e.g., friends and family) and social spaces proved essential for coping with the violence. Study 3 outlines the theoretical framework of the SAFO Program, which consists of eight sessions structured around the following phases: Welcoming; Module 1 (Psychoeducation on relationship violence and formal support); Module 2 (Psychoeducation on minority stress); Module 3 (Psychoeducation on emotion identification and support networks); and Closure. The feasibility of the SAFO Program was evaluated through a pre- and post-test design, utilizing the DASS-21, EDE-A, and PEM-LGB-BR instruments, as well as participant satisfaction measures. Data were analyzed using descriptive statistics and the Jacobson and Truax Method for a preliminary assessment of clinically significant changes. Intervention fidelity was examined by two independent observers, with inter-rater reliability estimated via Cohen’s Kappa index. The results provided initial evidence of feasibility, demonstrating high acceptability, appropriateness, implementability, practicality, and protocol fidelity. Participants reported high satisfaction with the program, highlighting the therapeutic alliance as a central element for engagement and the sharing of experiences. The evaluators confirmed high implementation fidelity and satisfactory facilitator performance. These findings suggest that the SAFO Program holds potential for integration into psychosocial care services, although future studies with larger samples, greater participant diversity, experimental designs, and follow-up assessments are necessary to confirm its efficacy.
SAFO Program (Online Affirmative Empowerment Support): online individual intervention for lesbian women victims of intimate partner violence
Keywords: violência entre parceiros íntimos; relacionamento homossexual; lésbicas; intervenção; intimate partner violence; homosexual relationship; lesbians; intervention; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL; 3. Saúde e Bem-Estar